Multıplıcatıon lattıce modules - (:unkn) unknown (My University, 2011)
Let M be a lattice module over the multiplicative lattice L. An L -module M is called a multiplication lattice module if for every element N ∈ M there exists an element a ∈ L such that N=a1M. Our objective is to investigate properties of prime elements of multiplication lattice modules.
Keywords: Lattice modules; Maximal element; Multiplicative lattice; Prime element